A Synthetic Pathway to the 1,4-Dihydro-2H-3-benzoxocine System from Morita–Baylis–Hillman Cinnamyl Alcohols with 2,5-Dimethoxy-2,5-dihydrofuran via the Heck Reaction - Ahn, Sang-Hyun; Kim, Young Keun; Hyun, Jina; Lee, Kee-Jung (Synthesis, 2012)
A new synthetic method for methyl 2-methoxy-1-(methoxycarbonylmethyl)-1,4-dihydro-2H-3-benzoxocine-5-carboxylates was developed using the Heck reaction between 2,5-dimethoxy-2,5-dihydrofuran and methyl 2-(hydroxymethyl)-3-(2-iodophenyl)propenoates as a key step. The latter were readily obtained from the Morita–Baylis–Hillman reaction of iodobenzaldehydes with methyl acrylate through acetylation, rearrangement, and hydrolysis. The methyl 2-methoxy-1-(methoxycarbonylmethyl)-1,4-dihydro-2H-3-benzoxocine-5-carboxylates were converted into methyl 2-oxo-1,2,5,11b-tetrahydro-3aH-furo[3,2-a][3]benzoxocine-6-carboxylates on exposure to excess trifluoroacetic acid.
Keywords: Morita–Baylis–Hillman; Heck reaction; 1,4-dihydro-2H-3-benzoxocines; iodobenzaldehydes; 2,5-dimethoxy-2,5-dihydrofuran